Fungal endophytes from Thalassia testudinum show bioactivity against the seagrass pathogen, Labyrinthula spp. - Ugarelli, Kelly; Jagels, Annika; Choi, Chang Jae; Loesgen, Sandra; Stingl, Ulrich (Frontiers in Marine Science, 2024)
Thalassia testudinum has undergone die-offs in the past century due to seagrass wasting disease caused by Labyrinthula sp. Little is known about how seagrasses resist Labyrinthula infections, but metabolites that inhibit Labyrinthula were previously extracted from seagrass leaves. Furthermore, leaf fungal endophytes from seagrasses possess antipathogenic potential, but their activity against Labyrinthula is unknown. Here, we aimed to identify whether fungal endophytes of T. testudinum can aid in disease defense against Labyrinthula. Through Illumina amplicon sequencing of the leaves’ mycobiome, we identified fungi that are known to produce antimicrobials. We also isolated and extracted organic compounds from endophytes to test their anti-Labyrinthula potential using disk diffusion assays. There were 22 isolates that inhibited Labyrinthula, from which two isolates, Trichoderma sp. P1a and Diaporthe sp. M14, displayed strong inhibition. LC-HRMS/MS analysis determined the likely bioactive compounds of Trichoderma as peptaibols and of Diaporthe as cytosporone B. Cytosporone B was confirmed bioactive against Labyrinthula via disk diffusion assays. While these organisms are low in abundance in the mycobiome, this study demonstrates that seagrass endophytes have the potential to play an important role in defense against Labyrinthula.